Successful Music Performer's Personality Traits - Iușcă Dorina Geta (Sciendo, 2021)
Music-education practice has revealed the fact that, in order to become a successful music performer, not only certain physical and perceptive attributes (such as the amplitude of open palm, thoracic capacity, rhythmic accuracy, musical hearing), but a series of personality traits related to the complexity of social, cognitive and emotional activities associated to music performance are also needed. Scientific research focused on high quality music performers' personality traits has been generated by a series of stereotypes that had been developed across time in the musical world. For example, it has often been said (Woody, 1999) that trumpet players are proud, impetuous, detached and dominating, whereas woodwind players are more feminine, more intelligent and shyer. The present study aims to review the most relevant experiments related to the personality profile of the successful music performer. A growing body of research has discovered ten important traits: androgyny, originality, independence, self-motivation, perseverance, sensibility, high capacity of interpersonal communication, extroversion, the need for attention, and trait anxiety. I discuss about a series of educational implications of this personality profile in connection to the development of a successful career in academic music. Discovering and developing these traits early on could be an essential support in creating an exceptional educational path in vocal and instrumental music performance.